Bouncing out of the banking system: An empirical analysis of involuntary bank account closures - Campbell, Dennis; Asís Martínez-Jerez, F.; Tufano, Peter (Journal of Banking & Finance, 2012)
Using a new database, we document the determinants of involuntary consumer bank account closures. During 2001–2005, approximately 30 million debit accounts were involuntarily closed for excessive overdrafting. We focus on multiple factors to explain this phenomenon: household economics and financial decision-making ability, social capital, bank policies, and the alternative financial services sector. Involuntary closures are more frequent in US counties with a larger fraction of single mothers, lower education levels, lower wealth, and higher unemployment. Closures are higher in communities with high property crime rates and low electoral participation. Bank policies have an independent relation to closures, with counties having more competitive banking markets and more multi-market banks experiencing higher closure rates; bank structure also seems to affect the speed at which banks adjust their policies to changes in household income. Finally, using both national data and a state-level shift in regulation, we find evidence that access to payday lending leads to higher rates of involuntary account closure.